The effects of different multidirectional plyometric sequences on shooting, balance, and neuromuscular performance in professional male basketball players - Seifeddine Brini; Fatma Hilal Yagin; Julio Calleja-González; Pierpaolo Sansone; Georgian Badicu; Anissa Bouassida; Carlo Castagna; Gianpiero Greco; Abdullah F. Alghannam; Luca Paolo Ardigò; Anne Delextrat (PLoS ONE, 2025)
Objective Repeated multidirectional jumps are highly specific movements in basketball, which may be important to integrate the training routine. Accordingly, this study aimed to assess the effects of three different multidirectional plyometric jumping sequences on shooting, balance, and neuromuscular performance in professional, male basketball players. Methods Eighteen players underwent familiarization and baseline performance assessments in an initial session. Players then completed 21 visits in a randomized, counterbalanced manner. Each visit involving 10 repetitions of one of three different multidirectional plyometric protocols followed by a single performance test (countermovement jump (CMJ), squat jump (SJ), five jump (FJT), change-of-direction T-test (CoD T), Stork balance (SBT), Y-balance (YBT), three-point shooting (3pts) tests). The first plyometric protocol (P1) consisted of a combination of vertical and horizontal jumps, the second protocol (P2) consisted of a combination of drop, lateral, and vertical jumps, and the third protocol (P3) consisted of a combination of drop, single-leg step-up, and horizontal jumps. Each session was separated by at least 48 h of rest and recovery time between repetitions was 20 s. Results Neuromuscular (CMJ, SJ, FJT and CoD T), body balance (SBT and YBT), and Shooting performances were significantly worse following each plyometric protocol compared to baseline (p < 0.001; d = 0.23–2.21). In addition, the majority of the measured performances were significantly lower following P3 compared to P1 and P2. Conclusions Basketball-specific performance was adversely influenced by repeated multidirectional plyometric routines. Incorporating these particular strategies into the training regimen to counteract the induced tiredness will be intriguing.